Optimizing conditions for oleanolic acid extraction from Lantana camara roots using response surface methodology - Banik R.M.; Pandey D.K. (My University, 2025)
Lantana camara is an ornamental plant used in traditional medicine for the treatment of various diseases. The roots of L. camara is a rich source of oleanolic acid which has shown anti-inflammatory, hepatoprotective, antitumor, antioxidant and anti-hyperlipidemic activity. Optimization of various extraction parameters using response surface methodology (RSM) was performed to assess maximum yield of oleanolic acid from L. camara roots. Plackett-Burman design criterion was applied to identify the significant effects of various extraction parameters such as temperature, time, mean particle size, solvent-solid ratio, solvent composition and number of extraction steps on extraction of oleanolic acid. Among the six variables tested extraction time, mean particle size, solvent-solid ratio and solvent composition were found to have significant effect on oleanolic acid extraction. Optimum levels of the significant variables were determined by using a central composite design. The most suitable condition for extraction of oleanolic acid was found to be a single step extraction at extraction temperature 35 °C, extraction time 55 min, solvent-solid ratio 55:1, mean particle size 0.5 mm and solvent composition 52.5% methanol in a methanol-ethyl acetate mixture. At these optimum extraction parameters, the maximum yield of oleanolic acid obtained experimentally (1.74% dry weight of root) was found to be very close to its predicted value of 1.69% dry weight of root. The mathematical model developed was found to fit well with the experimental data of oleanolic acid extraction. © 2007 Elsevier B.V. All rights reserved.